Kinds of Writing Difficulties in Academic Writing Faced by English Teachers of SMKN 8 Padang - Peragita Agdia; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2020)
Writing is a very complex skill and difficult to master. Difficulties in writing can be seen in various aspects of writing. There are various factors that cause difficulties in writing. This study aims to analyze the kind of writing difficulties faced by English teachers. In addition, this study also identifies factors that cause writing difficulties, namely psychological, socio-cultural, and linguistic factors. This research uses descriptive quantitative methods. Data were collected from 5 English teachers who teach at SMKN 8 Padang. In collecting data, the teachers were asked to write an academic essay with the topic of English for vocational high school students. To find out the factors that cause teacher difficulties in writing, data were collected through interviews. The results of the study aimed at teachers faced difficulties in every aspect of writing. they were difficulties in contents, organization, language use, and vocabulary. Then, the dominant factors that cause writing difficulties were psychological factors.